Design and synthesis of 14 and 15-membered macrocyclic scaffolds exhibiting inhibitory activities of hypoxia-inducible factor 1α. (15th January 2021) - Shimizu, Takahiro; Takahashi, Norihito; Huber, Vincent J.; Asawa, Yasunobu; Ueda, Hiroki; Yoshimori, Atsushi; Muramatsu, Yukiko; Seimiya, Hiroyuki; Kouji, Hiroyuki; Nakamura, Hiroyuki; Oguri, Hiroki
Graphical abstract: Abstract: Inspired by the privileged molecular skeletons of 14- and 15-membered antibiotics, we adopted a relatively unexplored synthetic approach that exploits alkaloidal macrocyclic scaffolds to generate modulators of protein–protein interactions (PPIs). As mimetics of hot-spot residues in the α-helices responsible for the transcriptional regulation, three hydrophobic sidechains were displayed on each of the four distinct macrocyclic scaffolds generating diversity of their spatial arrangements. Modular assembly of the building blocks followed by ring-closing olefin metathesis reaction and subsequent hydrogenation allowed concise and divergent synthesis of scaffolds 1–4 . The 14-membered alkaloidal macrocycles 2 –4 demonstrated similar inhibition of hypoxia-inducible factor (HIF)-1α transcriptional activities (IC50 between 8.7 and 10 µM), and 4 demonstrated the most potent inhibition of cell proliferation in vitro (IC50 = 12 µM against HTC116 colon cancer cell line). A docking model suggested that 4 could mimic the LLxxL motif in HIF-1α, in which the three sidechains are capable of matching the spatial arrangements of the protein hot-spot residues. Unlike most of the stapled peptides, the 14-membered alkaloidal scaffold has a similar size to the α-helix backbone and does not require additional atoms to induce α-helix mimetic structure. These experimental results underscore the potential of alkaloidal macrocyclic scaffolds featuring flexibly customizable skeletal, stereochemical, substitutional, and conformational properties for the development of non-peptidyl PPI modulators targeting α-helix-forming consensus sequences responsible for the transcriptional regulation.